Modern Directions in Early Biomarker Diagnostics of Parkinson's Disease : From Molecular Information Carriers to Non-Invasive Tissue Tests - Kryshtofik, Aliaksandr; Grygorowicz, Julia; Faria, Gabriela; Sas-Wyżykowska, Monika; Mykhalevych, Alina; Niedziela, Michał; Maruszak, Monika; Wyżykowska, Anna; Blachucik, Aleksandra; Subramoney, Akhil Roy (Quality in Sport, 2026)
Background: Parkinson’s disease (PD) is the fastest-growing neurological disorder globally. Traditional diagnosis, which relies on motor symptoms, is associated with a 15–24% error rate and occurs after significant loss of dopaminergic neurons. Early biomarker identification is essential for biological redefinition of PD and timely intervention. Objective: To synthesize evidence from the past five years on minimally invasive biomarkers and assess whether multimodal panels offer greater diagnostic precision than single tests. Methods: A systematic review of PubMed and Scopus (January 2021–January 2026) was conducted per PRISMA guidelines, including meta-analyses and original studies on α-synuclein seed amplification assays (SAA), neuronally derived extracellular vesicles (LIEVs), neurofilament light chain (NfL), and advanced imaging (OCT-A, MRI). Results: SAA exhibited 96% sensitivity in GBA1 mutation carriers and 98.6% in hyposmic individuals with dopaminergic deficits, but only 67.5% in LRRK2 carriers. Serum LIEV-associated α-synuclein distinguished prodromal cases with high precision (AUC=0.91). NfL predicted functional decline (OR=2.54) up to five years before diagnosis. Advanced neuroimaging and skin RT-QuIC tests showed diagnostic accuracies from 82% to 100%. Conclusion: PD diagnosis is shifting from clinical observation to biological profiling. Multimodal biomarker panels integrating molecular, microvascular, and imaging data provide the most precise risk stratification, enabling timely, targeted neuroprotective interventions by rehabilitation specialists.